Penggunaan Limbah Cangkang Bekicot (Achatina Fulica) sebagai Biokoagulan untuk Menurunkan Kandungan Fosfat, Kekeruhan, dan TSS pada Limbah Laundry - Narendra Satrya Priambudi; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Laundry services provide significant economic benefits to society, but can also generate waste that has the potential to harm the environment if not managed properly. Laundry waste contains various pollutants such as grease and chemical compounds such as sodium tripolyphosphate. One way to reduce phosphate levels and chemical oxygen demand (COD) in laundry waste is to use the principles of coagulation and flocculation. In this research, the coagulants used came from snail and crab shells as an alternative to chemical coagulants, which have a negative impact on the environment and human health. The process of producing biocoagulant from snail shells involves three stages, namely deproteination, demineralisation and deacetylation. This research aims to reduce three parameters of laundry waste, namely turbidity, total suspended solids (TSS) and phosphate. The research results showed that biocoagulant from crab shells was more effective in reducing these three parameters than biocoagulant from snail shells. This is due to a higher degree of deacetylation in crab shells, which is 84%, compared to 72% in snail shells. The high level of deacetylation in crab shell makes it more effective at binding ions, resulting in more floc being produced